2012
DOI: 10.1128/jvi.06936-11
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Myxoma Virus Plaque Phenotype by Vaccinia Virus Protein F11

Abstract: Vaccinia virus (VACV) produces large plaques consisting of a rapidly expanding ring of infected cells surrounding a lytic core, whereas myxoma virus (MYXV) produces small plaques that resemble a focus of transformed cells. This is odd, because bioinformatics suggests that MYXV carries homologs of nearly all of the genes regulating Orthopoxvirus attachment, entry, and exit. So why does MYXV produce foci? One notable difference is that MYXV-infected cells produce few of the actin microfilaments that promote VACV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…Lastly, by stimulating infected cell migration and the formation of long neurite-like projections, F11 enhances the spread of infection by increasing viral contact with more non-infected cells (Cordeiro et al, 2009;Valderrama et al, 2006). The ability of F11 to promote viral spread has also been elegantly illustrated using Myxoma virus, which lacks a related homologue (Irwin and Evans, 2012). Irwin et al found that a recombinant Myxoma virus expressing F11 is more effective in its cell-to-cell spread, as plaques expand ∼6 fold faster and are four times larger than controls after 4 days (Irwin and Evans, 2012).…”
Section: F11 Enhances Viral Spread By Inhibiting Rhoa Signallingmentioning
confidence: 97%
See 1 more Smart Citation
“…Lastly, by stimulating infected cell migration and the formation of long neurite-like projections, F11 enhances the spread of infection by increasing viral contact with more non-infected cells (Cordeiro et al, 2009;Valderrama et al, 2006). The ability of F11 to promote viral spread has also been elegantly illustrated using Myxoma virus, which lacks a related homologue (Irwin and Evans, 2012). Irwin et al found that a recombinant Myxoma virus expressing F11 is more effective in its cell-to-cell spread, as plaques expand ∼6 fold faster and are four times larger than controls after 4 days (Irwin and Evans, 2012).…”
Section: F11 Enhances Viral Spread By Inhibiting Rhoa Signallingmentioning
confidence: 97%
“…The ability of F11 to promote viral spread has also been elegantly illustrated using Myxoma virus, which lacks a related homologue (Irwin and Evans, 2012). Irwin et al found that a recombinant Myxoma virus expressing F11 is more effective in its cell-to-cell spread, as plaques expand ∼6 fold faster and are four times larger than controls after 4 days (Irwin and Evans, 2012). The expression of F11 also improves the oncolytic efficacy of Myxoma by increasing viral spread in tumours and prolonging the survival of mice (Irwin et al, 2013).…”
Section: F11 Enhances Viral Spread By Inhibiting Rhoa Signallingmentioning
confidence: 99%
“…However, it is notable that knocking down LIMK2, which would be expected to destabilize the actin cytoskeleton (99), and DIAPH1, which would disrupt adherens junctions (100), also promotes MYXV growth. We recently showed that MYXV has difficulties in disrupting the cortical actin layer during exit, and this can be partially ameliorated by incorporating the VACV F11L gene (101). This provides some rationale in support for the later structural hypothesis, although the two biological effects are not mutually exclusive.…”
Section: Resultsmentioning
confidence: 78%
“…However, in a murine model bearing transplanted human gliomas on both sides of the brain, single intratumoral injection of MYXV could eliminate the tumor mass only in the hemisphere in which MYXV was administered, indicating that the virus did not efficiently spread to the tumors in the contralateral hemisphere (102). The VV F11 protein promotes virus exit from an infected cell by inhibiting Rho signaling, which maintains the integrity of the cortical actin layer (112). Irwin & Evans (112) showed that a recombinant MYXV expressing the VV F11L gene (MYXV-F11L) replicates more efficiently than wild-type MYXV in monkey or rabbit cell lines.…”
Section: Myxoma Virus Oncolytic Virotherapymentioning
confidence: 99%
“…The VV F11 protein promotes virus exit from an infected cell by inhibiting Rho signaling, which maintains the integrity of the cortical actin layer (112). Irwin & Evans (112) showed that a recombinant MYXV expressing the VV F11L gene (MYXV-F11L) replicates more efficiently than wild-type MYXV in monkey or rabbit cell lines. In a variety of human cancerous cell lines, MYXV-F11L replicates more efficiently than control viruses (113).…”
Section: Myxoma Virus Oncolytic Virotherapymentioning
confidence: 99%